2008
DOI: 10.3390/ijerph5040213
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Microorganisms Associated With Childhood Diarrhea in Low-and-Middle Income Countries: Case Study of Yaoundé – Cameroon

Abstract: Notwithstanding significant advancement in the understanding of pathogenesis and management, diarrheal illnesses remain one of the principal causes of global childhood mortality and morbidity. Infections account for most illnesses, with pathogens employing ingenious mechanisms to establish disease. In 2002, an interdisciplinary program “Populations et al. Espaces à Risques SANitaires” (PERSAN) was set up under the patronage of the Development Research Institute (IRD). Focused on health in Cameroon’s urban envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
23
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 47 publications
9
23
5
Order By: Relevance
“…The higher incidence of Campylobacter among children do not match with findings shown by Gascón et al,. and Lindblom et al, [22,23] who described low incidence among children but our findings matches to greater extent with work done by NguendoYongsi who had shown higher prevalence of Campylobacter among children <5 years [11].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The higher incidence of Campylobacter among children do not match with findings shown by Gascón et al,. and Lindblom et al, [22,23] who described low incidence among children but our findings matches to greater extent with work done by NguendoYongsi who had shown higher prevalence of Campylobacter among children <5 years [11].…”
Section: Discussionsupporting
confidence: 91%
“…The maximum sufferers were between 1 and 3 years of age. A similar pattern of age distribution has been found in earlier done studies [13,11].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…39,40 G. lamblia prevalence in our study was higher compared with studies conducted in Mozambique (2.5%), Cameroon (13.2%), Tanzania (14.0%) and Kenya (16%). 6,22,37,41 All the aforementioned studies applied microscopy for diagnosing G. lamblia. In our study, we identified G. lamblia by both methods (microscopy and the antigen rapid test) and found that more than half of the positive cases were detected only by the antigen rapid test.…”
Section: Discussionmentioning
confidence: 99%
“…Parasites have been introduced as the third rank cause of diarrhea in developing countries. Among viruses, rotavirus has been known as the cause of diarrhea in more than 50% of children and other viruses play insignificant roles in causing diarrhea (10)(11)(12). In this study, pathogenic agents were detected in 19.6% of the patients.…”
Section: Discussionmentioning
confidence: 65%